Oxidation of [U‐13C]glucose in the human brain at 7T under steady state conditions - Cheshkov, Sergey; Dimitrov, Ivan E.; Jakkamsetti, Vikram; Good, Levi; Kelly, Dorothy; Rajasekaran, Karthik; DeBerardinis, Ralph J.; Pascual, Juan M.; Sherry, A. Dean; Malloy, Craig R. (Magnetic resonance in medicine, 2017)
Purpose Disorders of brain energy metabolism and neurotransmitter recycling have been implicated in multiple neurological conditions. 13C magnetic resonance spectroscopy (13C MRS) during intravenous administration of 13C‐labeled compounds has been used to measure turnover rates of brain metabolites. This approach, however, requires prolonged infusion inside the magnet. Proton decoupling is typically required but may be difficult to implement with standard equipment. We examined an alternative approach to monitor glucose metabolism in the human brain. Methods 13C‐enriched glucose was infused in healthy subjects outside the magnet to a steady‐state level of 13C enrichment. Subsequently, the subjects were scanned at 7T for 60 min without 1H decoupling. Metabolic modeling was used to calculate anaplerosis. Results Biomarkers of energy metabolism and anaplerosis were detected. The glutamate C5 doublet provided information about glucose‐derived acetyl‐coenzyme A flux into the tricarboxylic acid (TCA) cycle via pyruvate dehydrogenase, and the bicarbonate signal reflected overall TCA cycle activity. The glutamate C1/C5 ratio is sensitive to anaplerosis. Conclusion Brain 13C MRS at 7T provides information about glucose oxidation and anaplerosis without the need of prolonged 13C infusions inside the scanner and without technical challenges of 1H decoupling, making it a feasible approach for clinical research. Magn Reson Med 78:2065–2071, 2017. © 2017 International Society for Magnetic Resonance in Medicine.